Increased Oxygen Desaturation Time During Sleep Is a Risk Factor for NASH in Patients With Obstructive Sleep Apnea: A Prospective Cohort Study - Landete, Pedro; Fernández-García, Carlos Ernesto; Aldave-Orzaiz, Beatriz; Hernández-Olivo, Marta; Acosta-Gutiérrez, Carmen M.; Zamora-García, Enrique; Ancochea, Julio; González-Rodríguez, Águeda; García-Monzón, Carmelo (Frontiers in Medicine, 2022)
Introduction. Given that obstructive sleep apnea (OSA) is commonly associated with metabolic disorders, in this prospective study we sought to determine the prevalence and risk factors for hepatosteatosis, steatohepatitis (NASH) and advanced liver fibrosis in patients with clinical and polygraphic criteria of OSA (n=153) and in subjects with normal lung function parameters (NLP, n=43). Methods. Hepatosteatosis, NASH and advanced liver fibrosis was determined by blood-based non-invasive tools, such as fatty liver index and hepatic steatosis index, a serum lipidomic (OWLiver™) test and three distinct fibrosis algorithms, respectively. Logistic regression models adjusted by potential confounders were performed to evalu-ate risk factors. Results. Insulin resistance and dyslipidemia were more frequent in patients with OSA than in subjects with NLP. Prevalence of hepatosteatosis was significantly higher in OSA patients than in subjects with NLP. NASH was also found more frequently in pa-tients with OSA than in subjects with NLP. In contrast, advanced liver fibrosis was rarely detected in the entire study population and no significant differences were observed between OSA patients and subjects with NLP. Besides male gender, increased body mass index and presence of type 2 diabetes, percentage of sleep time with oxygen sat-uration less than 90% (Tc90%) was the only polygraphic variable significantly associat-ed with NASH in patients with OSA. Conclusions. This study shows that hepatosteatosis and NASH are highly prevalent in patients with OSA and indicates that those with a Tc90% higher than 10% are at in-creased risk for NASH.